The Economic Impact of a Sporting Event: A Regional Approach - Ronald William McQuaid; Malcolm S Greig (European Regional Science Association (ERSA), 2003)
This paper aims to estimate the economic impact of a large one-day international sporting event on both a regional and a city economy. In addition, it seeks to investigate the regional origins of visitors to the event, and investigates the relationship between residence and expenditure. The importance of sporting events to regional economies is recognised, but can be difficult to quantify due to the scale and nature of the data required. This analysis draws on over 5,000 spectator interviews conducted at the five one-day rugby internationals (Scotland versus England, France, Romania, South Africa and Fiji) held in Edinburgh, Scotland, during 2002. As such it represents one of the largest databases of its kind in Europe. Spectators were asked about their expenditure, residence, accommodation and attitudes to future visits. Findings were triangulated using a parallel survey of business turnover. The survey data is used to estimate the economic impact on both the wide region (Scotland) and the city region (Edinburgh). Our findings indicate that each match may be worth around 20m to the Scottish economy and 12m to the city of Edinburgh economy. We argue that although this appears large, the methodology used may have resulted in an estimate that is slightly conservative if anything. This points to a greater need for local, regional and national government to exploit the potential that such events can have. We also found that the origin profile of spectators differs between matches, naturally reflecting the origins of the visiting crowd, but more importantly there are also notable regional differences in expenditure patterns among visitors from each nation. We examine the possible reasons for this and the implications for regional and city tourism marketing strategies.
Keywords: 330